Study on AgInZnS-Graphene Oxide Non-toxic Quantum Dots for Biomedical Sensing - Song, Chi; Luo, Haoyue; Lin, Xiaogang; Peng, Zhijia; Weng, Lingdong; Tang, Xiaosheng; Xu, Shibin; Song, Ming; Jin, Lifeng; Zheng, Xiaodong (Frontiers in Chemistry, 2020)
In recent years, non-toxic quantum dot has appealed to much attention in biomedical fields. However, the inherent cytotoxicity of QDs is painful circumscribes the biomedical application, which has become one of the maximum drawbacks. In this paper, a non-toxic and water-soluble quantum dot AgInZnS-GO by graphene oxide was synthesized. Also, a simple model of state complex was established, which is produced by the combination of the quantum dot and protein. The interaction between AIZS-GO QDs and human serum albumin (HSA) has significant meaning in vivo biological application. Herein, the binding of AIZS-GO QDs and HSA were researched by fluorescence spectra, Uv-visible absorption spectra, FT-IR spectra and circular dichroism (CD) spectra. The results of fluorescence spectra demonstrate AIZS-GO QDs have obvious fluorescence quenching effect on HSA. The quenching mechanism was static quenching, which implied that some kinds of complex were produced by the binding of QDs and HSA. These results were further proved by Uv-visible absorption spectroscopy. The Stern-Volmer quenching constant Ksv at various temperatures (298 K, 303 K, 308 K) were acquired from analyzing Stern-Volmer plots of the fluorescence quenching information. Van’t Hoff equation could describe the thermodynamic parameters, which demonstrated that the van der Waals and hydrogen bonds had an essential effect on the interaction. FT-IR spectra and CD spectra further indicate that AIZS-GO QDs can alter the structure of HSA. These spectral methods show that the quantum dot can combine well with HSA. The experimental results showed that AgInZn-GO water-soluble quantum dots have good biocompatibility, which can be combined with proteins to form new compounds and have no cytotoxicity and biological practicability. It provides an important basis for the combination of quantum dots and specific proteins and fluorescent labeling.